Multinationals in Sub-Saharan Africa: Domestic linkages and institutional distance - Lucia Pérez-Villar; Adnan Seric (Kiel Institute for the World Economy (IfW), 2014)
This paper analyzes the role of institutional distance in the establishment of domestic linkages by multinational enterprises in a cross- section of 19 Sub- Saharan countries. Investors' familiarity with formal and informal procedures in the host country lowers uncertainty and facilitates networking with local firms. Hence, a similar degree of institutional development boosts linkages between domestic firms and multinationals. Using a novel dataset from the 2010 Africa Investor Survey by UNIDO we find that institutional distance in terms of contract enforcement deters the domestic linkage in host countries with worse institutions relative to the origin country. Additionally, institutional distance matters more for multinationals from the north. The paper sums to the literature on domestic linkages by including the understudied institutional dimension, to the still scarce literature on South- South FDI in least developed countries and contributes to the definition of clearer targets for foreign investment policies.
Keywords: F14; F23; O19; 330; Multinational Firms; South- South; Backward Linkages; Institutions